2019
DOI: 10.4081/monaldi.2019.1112
|View full text |Cite
|
Sign up to set email alerts
|

Scope and new horizons for implementation of m-Health/e-Health services in pulmonology in 2019

Abstract: The reason for this review based on the results of many meta- analyses is the great assessed difference in the methods of most studies in e-Health, telemedicine and tele-rehabilitation. It consists of different understanding of new terms, using different hard- and software, including criteria, different methodology of patient’s treatment and its evaluation. This status suggests that first of all m-Health/e-Health requires a unique ontology of terms using and methodology of studies comparing. In this review we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Poor adherence can adversely affect the trajectory of the disease and lead to suboptimal clinical benefits together with inefficient utilisation of healthcare resources. Remote monitoring m-health/e-health technologies provide patients with the tools they need to improve adherence such as regular reminders, usage monitoring, medication-specific education and facilitating virtual visits [ 52 , 53 ].…”
Section: Group 104: M-health/e-healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor adherence can adversely affect the trajectory of the disease and lead to suboptimal clinical benefits together with inefficient utilisation of healthcare resources. Remote monitoring m-health/e-health technologies provide patients with the tools they need to improve adherence such as regular reminders, usage monitoring, medication-specific education and facilitating virtual visits [ 52 , 53 ].…”
Section: Group 104: M-health/e-healthmentioning
confidence: 99%
“…Virtual consultation using tele-conferencing technologies provides a safe and convenient modality to monitor the health of patients, especially during a pandemic [ 52 ]. H arkness et al [ 59 ] demonstrated the clinical usefulness of “virtual wards” in the UK to facilitate the safe discharge of COVID-19 patients.…”
Section: Group 104: M-health/e-healthmentioning
confidence: 99%
“…V. Poberezhets discussed new horizons in digital technologies for respiratory medicine where an ontological structure of digital medicine was presented ( figure 1 ) [ 21 ]. The use of artificial intelligence (AI) and machine learning has been employed to improve diagnostic yield and decrease workload in thoracic imaging [ 22 , 23 ], histopathology and cytology [ 24 , 25 ].…”
Section: Group 901: Respiratory Function Technologists and Scientistmentioning
confidence: 99%
“…Telemedicine is the remote delivery of healthcare services, through electronic communication, that allows healthcare providers to evaluate, diagnose and treat patients without the need for an in-person visit [ 2 ]. Beginning more than 40 years ago with hospitals extending their services to patients in remote locations, telemedicine has grown rapidly and has become an integrated part of specialty departments, hospitals, private doctor offices, and home health care [ 3 ]. Telemedicine applications include, among others, (a) virtual care visits, (b) telemonitoring, (c) telerehabilitation, (d) teleconsultation, (e) telepathology, (f) teleradiology, and (g) remote assistance and patient management [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%